Synthesis and Characterization of some Mixed–Ligand Complexes Containing Salicylic Acid and Pyridine with some Metal Ions - Awad, Sana H (Al-Nahrain Journal of Science, 2012)
Some metal ions (Mn+2,Fe+2,Co+2,Cu+2,Zn+2,Cd+2and Hg+2) Complexes of salicylic acid (SA) and Pyridine (Py) were Synthesized and characterized by elemental analysis FT-IR and uv-Visible Spectra and conductive measurements From the results obtained, the following general formula are given for the prepared complexes [M+n(SA)2(Py)2].XH2O, where M+n  Mn+2, Fe+2, Co+2, Cu+2, Zn+2, Cd+2, Hg+2), n  2, X  0, 0, 6, 0, 5, 6, 6; (SA)  ligand ion (Salicylato), (Py) Pyridine